High spatial and temporal resolution Ca2+ imaging of myocardial strips from human, pig and rat - Borysova, L; Ng, YYH; Wragg, ES; Wallis, LE; Fay, E; Ascione, R; Dora, KA (Springer Nature, 2021)
Ca2+ handling within cardiac myocytes underpins coordinated contractile function within the beating heart. This protocol enables high spatial and temporal Ca2+ imaging of ex vivo multicellular myocardial strips. The endocardial surface is retained, and strips of 150–300-µm thickness are dissected, loaded with Ca2+ indicators and mounted within 1.5 h. A list of the equipment and reagents used and the key methodological aspects allowing the use of this technique on strips from any chamber of the mammalian heart are described. We have successfully used this protocol on human, pig and rat biopsy samples. On use of this protocol with intact endocardial endothelium, we demonstrated that the myocytes develop asynchronous spontaneous Ca2+ events, which can be ablated by electrically evoked Ca2+ transients, and subsequently redevelop spontaneously after cessation of stimulation. This protocol thus offers a rapid and reliable method for studying the Ca2+ signaling underpinning cardiomyocyte contraction, in both healthy and diseased tissue.